Connections between steel-concrete composite column and steel beam - Andrej Mudrov (Mokslas: Lietuvos Ateitis, 2022)
Composite steel-concrete columns of circular cross-section have high strength and stiffness, which theoretically could help to reduce the cost of construction, but their advantages are still widely unexploited. In comparison with other constructions, composite columns account for a diminutive market share. One of the many reasons for this, is the complexity of connections that may require on-site welding, which not only slows down the construction, but also makes it more expensive. With the recent extensive development of blind bolts, new design options for the tube columns emerged. Such bolted joints would eliminate onsite welding and speed up installation. In this review a particular attention is paid to the circular columns, because these columns have the least studied connections. This article reviews the most recent stage in the development of the connections between steel-concrete composite columns and steel beams, as well as provides provisions for using such connections and outlines the directions for further research.